Повесть Кампанила святого Марка М. Шишкина в интернет-журнале, на сцене и в радиоэфире: Интерпретация позиции автора - Кравченкова, Евгения (Acta Polono-Ruthenica, 2021)
Mikhail Shishkin wrote St Mark’s Campanile (2011) as a documentary short novel, based on letters of the socialist couple Franz and Lidia. Director Nikita Kobelev presented an audio version and a theatrical interpretation of the novel in 2012. In three variants of the same text the authorial intent can be expressed through the direct speech of the author, title, irony and composition. In the present article St Mark’s Campanile is considered as a metatext in which the character is a writer and, thus, the authorial intent is hidden behind the character’s thoughts and ideas. Kobelev, on the contrary, emphasizes his point of view on the characters’ actions and ideals. In the radio drama he analyses achievements and losses of a woman involved in revolutionary activities, and in the stage performance the director focuses on Franz’s dream of family happiness.